Architectural design of an advanced naturally ventilated building form - Kevin Lomas (2007)
Advanced stack-ventilated buildings have the potential to consume much less energy for space conditioning than typical mechanically ventilated or air-conditioned buildings. This paper describes how environmental design considerations in general, and ventilation considerations in particular, shape the architecture of advanced naturally ventilated (ANV) buildings. The attributes of simple and advanced naturally ventilated buildings are described and a taxonomy of ANV buildings presented. Simple equations for use at the preliminary design stage are presented. These produce target structural cross section areas for the key components of ANV systems. The equations have been developed through practice-based research to design three large educational buildings: the Frederick Lanchester Library, Coventry, UK; the School of Slavonic and East European Studies, London, UK; the Harm A. Weber Library, Elgin, near Chicago, USA. These buildings are briefly described and the sizes of the as-built ANV features compared with the target values for use in preliminary design. The three buildings represent successive evolutionary stages: from advanced natural ventilation, to ANV with passive downdraught cooling, and finally ANV with HVAC support. Hopefully the guidance, simple calculation tools and case study examples will give architects and environmental design consultants confidence to embark on the design of ANV buildings.